Straight talk on investing : - Brennan, Jack (John Wiley & Sons, 2002)
Brennan offers readers a plain-speaking primer on how to build a sensible long-term investment portfolio. While Brennan applauds the "democratization of Wall Street" that has allowed anyone to become an investor, he notes that the resultant explosion of investment advice includes much that's "dangerous to your wealth." This guide, he says, is the book he himself would have liked to have received when he began his personal investments. The emphasis is on long-term goals and balance rather than playing the market: throughout, Brennan cautions against micro-managing the profile or getting sucked into fads. Though his guidance comes well after the bursting of the stock market bubble, the principles stated within would have steadied the nervous investor through the phenomenon and its nasty aftermath.